THE CORRELATION OF LISTENING COMPREHENSION TO THE STUDENTS’ SPEAKING PERFORMANCE IN EFL CONTEXT AT UNIVERSITAS DAYANU IKHSANUDDIN BAUBAU - Suharja Suharja (English Education Journal, 2020)
The goal of this study was to find out the connection between the listening comprehension of students and their speaking performance. Tests were carried out on the tools and the information was evaluated using basic regression analysis. 95 students of Dayanu Ikhsanuddin University were given a measure of listening awareness and speaking skill tests. The result of data analysis indicated that there is a significant correlation between listening comprehension and speaking performance. The probability value is 0.021, because p < 0.05 then Ho was rejected and Ha was accepted. It can be concluded that students’ listening comprehension and speaking performance denoted a positive correlation.